The Model of Responsible Managerial Education in Conditions of Economy Transformation - I. L. Vladimirova; G. Yu. Kallaur; A. A. Tsygankova (Вестник Российского экономического университета имени Г. В. Плеханова)
Today’s universities’ need to adapt to transformation processes is formed by such phenomena as digitalization and globalization of economy, fast growth in competition in the field of education services, the development of innovation technologies and communication means. Being the foundation of human capital development for all industries of economy the education environment today should meet the acute requirements of labour market in highly qualified workers, foster establishment of strong links with national and international academic communities and successful positioning in global education and professional business-space. Taking into account the UN initiative ‘Principles of Responsible Managerial Education’ (2007), which is considered as an approach to promotion of principles of sustainable development in universities implementing education programs of managerial profile, the university becomes a key element in shaping a new education eco-system. It defined the aim of the present research, which includes analysis of the key trends in the development of today’s system of managerial personnel training and factors that stipulated them on global and national level. On the basis of 25-years’ experience of the chair ‘Management of Capital Group Projects and Programs’ of the Russian Plekhanov University of Economics the authors studied the key stages of transformation processes of developing the system of higher education in Russia in post-soviet period. In conclusion they formulated new characteristics of the model of responsible managerial education being shaped.